2001
DOI: 10.1007/s11663-001-0126-3
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of laser-spot-weld shape by numerical analysis and neural network

Abstract: The finite element method (FEM) and neural network were applied for predicting the bead shape in laser spot welding of type 304 thin stainless steel sheets. The parameters of pulsed Nd:YAG laser spot welding such as pulse energy, pulse duration, sheet metal thickness, and gap between sheets were varied for various experiments and numerical simulations. The penetration depth and nugget size of spot welds measured for specimens without gap were compared with the calculated results to verify the proposed finite e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 10 publications
(14 reference statements)
1
19
0
Order By: Relevance
“…4 illustrates that the penetration depth, bead width and bead length all increase as the laser energy increases at the same incident angle of 30-75 • . It also indicates the slope of all characteristic length decrease as laser energy increases, similar results were found in Chang and Na's study [4]. Fig.…”
Section: The Characteristic Lengths Of Weld Spotsupporting
confidence: 86%
See 2 more Smart Citations
“…4 illustrates that the penetration depth, bead width and bead length all increase as the laser energy increases at the same incident angle of 30-75 • . It also indicates the slope of all characteristic length decrease as laser energy increases, similar results were found in Chang and Na's study [4]. Fig.…”
Section: The Characteristic Lengths Of Weld Spotsupporting
confidence: 86%
“…The hole due to material vaporization is assumed to be a conelike shape in the vertical welding [4], its volume is estimated by…”
Section: Volume Analysis Of Welded Spotmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the model researchers calculated temperature distribution, penetration depth, weld bead size and geometry which are in good agreement with experimental result. Chang and Na [68], reported the development of a combined model of finite element analysis and neural network for prediction of weld bead geometry during laser spot welding of AISI 304 stainless steel. Authors used heat conduction theory for finite element Methods and showed that thermal & mechanical aspects can be decoupled assuming that the dimensional changes during laser spot welding are insignificant.…”
Section: Investigation On Other Materialsmentioning
confidence: 99%
“…Recently, a number of numeri cal models have been developed to study thermal and mechanical phenomena during laser processes. These models were used to evaluate temperature distributions and to predict the weld pool shape, the melting zone, and the dimensions of the HAZ [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], In some studies, a fully or sequentially coupled thermal-stress analysis was also carried out to determine the thermal deformations-distortions and the residual stress-strain fields [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Most of these investigations are limited to problems associated with continuous or single spot laser welding in butt-, lap-, or T-joint specimens; the mechanical effects of LSW in manufactur ing processes of large industrial structures, such as solar absorb ers, have not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%